E-Learning in COVID-19 Situation: Students’ Perception - Sakkir, Geminastiti; Dollah, Syarifuddin; Ahmad, Jamaluddin (EduLine: Journal of Education and Learning Innovation, 2021)
COVID-19 pandemic era has changed human life in the world. In education side, the learning process is forced to be carried out through full online (E-learning) since this pandemic era. There are many studies conducted on students’ perceptions of using E-learning to learn the English language while this challenges era. So, the researchers also want to conduct a study about it. The objective of this study was to investigate the students’ perceptions on the use of E-learning while COVID-19 pandemic era. Data were collected using a questionnaire that collected background information of participants and a five-point Likert scale to gauge the students’ perception use of the E-learning in EFL classroom while pandemic COVID-19 era. Findings from this research indicate that the most of students showed a negative perception toward to use E-learning in the EFL process. It was proved by the results of students’ perception. There is only 1 student who strongly agrees with the current e-learning process or said that the E-learning in pandemic COVID-19 era is effective, there are 10 students who said the E-learning is less effective, 1 students say they are moderate (4%), 12 students said E-learning is not effective and 3 student said E-learning is very not effective. There are many factors influenced the students’ perception on the use of E-learning media in COVID-19 pandemic era such as, the signal and network connection; limit of quota and expensive; lack of lecturers methods; lack of students’ motivation; limitation of time; and lack of interaction.